Human Factors and Ergonomics in Healthcare: Industry Demands and a Path Forward. (February 2022) - Keebler, Joseph R.; Rosen, Michael A.; Sittig, Dean F.; Thomas, Eric; Salas, Eduardo
This article reviews three industry demands that will impact the future of Human Factors and Ergonomics in Healthcare settings. These demands include the growing population of older adults, the increasing use of telemedicine, and a focus on patient-centered care. Following, we discuss a path forward through improved medical teams, error management, and safety testing of medical devices and tools. Future challenges are discussed.